2010
DOI: 10.3113/fai.2010.0542
|View full text |Cite
|
Sign up to set email alerts
|

Partial Fibulectomy for Symptomatic Fibular Nonunion

Abstract: Level of Evidence: V, Expert Opinion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The age range was from ten years to 72 years. The range of follow-up (from three months to 23 years) was reported in eight articles only [1][2][3][4][7][8][9][10]. In combined tibia/fibula fractures, fibular nonunion occurred more commonly when the tibia was stabilised with intramedullary nails (5.5 % in the nail group, 4.14 % in the plate group, and none in the conservative group) [1,4,5].…”
Section: Incidencementioning
confidence: 99%
See 2 more Smart Citations
“…The age range was from ten years to 72 years. The range of follow-up (from three months to 23 years) was reported in eight articles only [1][2][3][4][7][8][9][10]. In combined tibia/fibula fractures, fibular nonunion occurred more commonly when the tibia was stabilised with intramedullary nails (5.5 % in the nail group, 4.14 % in the plate group, and none in the conservative group) [1,4,5].…”
Section: Incidencementioning
confidence: 99%
“…CT scan as a diagnostic radiological investigation was used in only less than 20 % of the cases. CT scan was more useful in cases with suspected concomitant incomplete union of the tibia [4] and in cases of Weber B type ankle fractures [6,[8][9][10] where the extent of fibular union was sometimes difficult to appreciate on plain X-rays (Fig. 4).…”
Section: Radiological Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…These include further conservative management, bone stimulation, external fixation, percutaneous drilling, bone grafting and ORIF with or without bone grafting, arthrodesis, excision and segmental resection [3,8]. Segmental resection, however, is not recommended for fractures close to the ankle joint, such as this patient's [8]. Bhadra et al [3] also provided a treatment algorithm that recommends ORIF with bone grafting for atrophic nonunions of the distal third fibula, which is what we did.…”
Section: Discussionmentioning
confidence: 86%
“…In a systematic review of fibula non-unions, Bhadra et al [3] reviewed the treatment options found in the literature [3]. These include further conservative management, bone stimulation, external fixation, percutaneous drilling, bone grafting and ORIF with or without bone grafting, arthrodesis, excision and segmental resection [3,8]. Segmental resection, however, is not recommended for fractures close to the ankle joint, such as this patient's [8].…”
Section: Discussionmentioning
confidence: 99%